My Dream, My Rules: Can Lucid Dreaming Treat Nightmares? - de Macêdo, Tainá Carla Freitas; Ferreira, Glescikelly Herminia; de Almondes, Katie Moraes; Kirov, Roumen; Mota-Rolim, Sérgio Arthuro (Frontiers in Psychology, 2019)
Nightmares are frightening dreams, usually involving threats to survival, security, and self-esteem. Intense and recurring nightmares cause significant distress and impairment in occupational and social functioning, as have been commonly observed in post-traumatic stress disorder, depression and anxiety. By contrast, during lucid dreaming (LD), subjects get insight that they are dreaming and may even control the content of their dreams. This possibility opens a way to help those who suffer from recurring nightmares through the re-signification of the dream scene, i.e., knowing that they are dreaming and having control over the dream content, lucid dreamers might be able to turn their nightmares into normal dreams, thereby assuring a restoring sleep. The aim of the present study is to review the literature on the use of LD as an auxiliary tool in the treatment of nightmares. We searched for original research articles in scientific databases using the keywords "lucid dream(s)" or "lucid dreaming" and "nightmare(s)" or "recurring nightmare(s)". We observed that whereas LD may be a feasible aid in the treatment of patients with nightmares through minimizing their frequency, intensity and psychological distress, the available literature is still scarce and does not provide consistent results. We conclude therefore that more research is clearly warranted for a better estimation of the effective conductance and therapeutic outcome of LD treatment in clinical practice.